Description of Student Attitudes: Enjoyment in Learning Physics and Interest in More Time Studying Physics - Mirawati, Mirawati; Sikarni, Weni (Schrödinger: Journal of Physics Education, 2023)
Purpose of the study: The purpose of this study is to describe students’ attitudes toward learning Physics by looking at the level of enjoyment of students in learning Physics and their interest in increasing the time spent studying Physics at SMAN 08 Batanghari. The students’ attitudes were analyzed from the indicators of students’ attitudes towards Physics, namely the students’ pleasure in learning Physics and their interest in increasing their time to study Physics. Methodology: The research sample data consisted of all classes X, XI and XII IPA. The sampling technique of this study is the total sampling technique. The sample used was 150 students. This type of research is Quantitative with a survey method. The instrument used is an attitude questionnaire. Data analysis in this study used descriptive statistics. Main Findings: The research results obtained showed that the indicator of enjoyment in learning Physics had the highest percentage of 47.3%, 71 students in the good category, and the indicator of interest in increasing the time to study Physics had the highest percentage, 62.0%, 93 students in the moderately good category. This shows that students’ enjoyment in learning can be seen from the amount of time students spend studying Physics. Novelty/Originality of this study: The novelty of this study is to identify students’ attitudes through indicators of students’ enjoyment of the Physics subject at SMA Negeri 08 Batanghari which aims to increase students’ curiosity and a sense of enthusiasm in understanding physics concepts. As well as increasing indicators of interest in physics subjects by increasing the time to study physics which aims to improve student achievement and learning outcomes.